Penerapan Prosedur Mediasi dalam Penyelesaian Sengketa Wakaf di Pengadilan Agama - Syufaat, Syufaat (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
Waqf has two dimensional meaning; the spiritual dimension that is taqarrub to Allah and the social dimension as the source of Islamic financial for the welfare of the people. Waqf disputes can be caused by several reasons; waqf land is not accompanied with a pledge; waqf is done on the basis of mutual trust so it has no legal proof and ownership. Currently, the choice to use the court is less effective in resolving disputes. Hence, the public ultimately chooses non-litigation efforts as a way to resolve the disputes. Mediation process is preferred by many as it is viewed to be the fairest way where none of the two parties wins or loses (win-win solution). It is also fast and cheap. This study is intended to examine how to solve waqf dispute with mediation model according to the waqf law, and how the application of mediation in the Religious Courts system